Effect of a cross flow sprayer and an air-carrier, axial-fan sprayer on the quality distribution, pest control and drift in an apple orchard - Magdalena, Jorge Carlos; Val Manterola, Luis; Di Prinzio, Alcides Pascual; Behmer, Sergio Néstor (2025)
In Argentina, the North Patagonian Region is the largest producing area of apples and pears of the Southern Hemisphere. In modern pomology, the study of new sprayer design to optimize pesticide delivery to fruit crops it is a priority. The aim of this research was to compare the efficiency of pesticide application between a conventional air-carrier sprayer (axial-fan) and a cross flow sprayer (4 cross-flow fans) using two volume rates, standard and 80 %. The results showed that the best performance was obtained with the cross flow sprayer. Control of Codling moth was more difficult inside than outside the canopy, since the fruit damage was near two fold in the later. However, under the test conditions the cross flow sprayer showed acceptable and uniform pesticide coverage inside the canopy, and at different tree heights (top, middle and bottom). The better spray distribution of the cross flow sprayer provided a good control of codling moth even at a reduced volume rate. The cross flow sprayer allowed to reduce exodrift losses beyond the top of the trees by 5to 8 fold, however, the endodrift within row increased.